Asymptomatic hepatitis B virus-positive patients visiting dental outpatient department in North India: A multicentric study - Richik Tripathi; Nidhi Singh; Prajesh Dubey; Himanshu Thakural; Dipti Samal; Abhishek Laha (Wolters Kluwer Medknow Publications, 2020)
Background: In India, it is estimated that nearly 3%-4% of the population is affected by hepatitis-B virus (HBV). During the initial stage of the disease, the patient is asymptomatic, and there is a possibility for cross infection to dental surgeons and to other patients. The purpose of this study was to find the incidence of such HBV-infected asymptomatic patients visiting dental clinics of North India. Materials and Methods: This prospective study was conducted in the outpatient department at five different centers of North India. Three centers in Uttar Pradesh, one centre in Bihar, and one centre in Himachal Pradesh. All the patients visiting dental OPD were advised hepatitis-B surface antigen (HbsAg) screening test day before dental procedure, and the procedure was planned on the next day or on the second day after reports were submitted. Those patients who were found positive for HbsAg were further tested for HBV DNA using polymerase chain reaction technique. Results: Five thousand patients were screened, of 5000 patients, 4840 patients submitted complete blood test reports. One thousand six hundred and ninety patients were female and 3150 patients were male. The male-to-female ratio was 1:2.5. Fifty patients were found to be hepatitis B positive. Thirty patients of hepatitis B were in early infective stage. It was found that forty patients were positive for HBV DNA, whereas ten patients were negative. Conclusion: Incidence of asymptomatic hepatitis-B positive patients visiting oral surgery outpatient department in North India is 1%. We recommend routine HbsAg testing and proper sterilization of dental instruments in all dental surgical procedures.